PKM YOGA PRANATAL DI DI POSYANDU MEKAR WILAYAH KERJA UPT BLUD PUSKESMAS TAPUNG HULU I - Endang Mayasari; Umi Mustikasari (COVIT (Community Service of Health), 2021)
During pregnancy, so that the body stays in shape, you can do sports. One of them is prenatal yoga, which is a type of yoga practice specifically designed for pregnant women. Besides being able to maintain health, this sport also makes pregnant women feel relaxed and calm. Weight gain will certainly occur during pregnancy, but excessive weight gain will certainly make it difficult during the delivery process later. Prenatal yoga practice can help pregnant women to maintain weight gain before giving birth. Yoga for pregnant women can increase the strength and flexibility of the body. Yoga movements for pregnant women make exercise for pregnant women a good exercise to practice breathing and help the labor process become calmer, easier, and smoother.